Sur la convergence de l'intégrale double de Laplace—Stieltjes et des series doubles de Dirichlet - Abdrakmanov, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Г. Абдрахманов. О сходимости двойного интервала Лапласа—Стилтьеса и двойных рядов ДирихлеV. Abdrachmanovas. Dvilypio Laplaso—Stiltieso integralo ir dvilypių Dirichle eilučių virškonvergavimo klausimu